Nomınal and Verbal Predıcate Use in Schızophrenıa - Айшегюль Озджан Вурал; Гюльмира Куруоглу (Психолінгвістика, 2020)
Objective. Schizophrenia’s first characteristics invokes the notion of disordered thought and language. Accordingly one of several diagnostic characteristics of schizophrenia is an impairment of verbal communication. To determine the detailed nature of  language impairments taking into consideration these problems the aim of the present study was to analyze nominal and verbal predicate use produced by schizophrenic patients and control group during their speech as both predicates require different processings.